Computerized neuropsychological profiles of South African versus US athletes: A basis for commentary on cross-cultural norming issues in the sports concussion arena - Shuttleworth-Edwards, A. B.; Whitefield-Alexander, V. J.; Radloff, S. E.; Taylor, A. M.; Lovell, M. R. (The Physician and Sportsmedicine, 2009)
Abstract: Computerized programs are widely used as part of the overall medical management of concussion in order to monitor recovery and facilitate safe return-to-play decisions. Typically, neurocognitive profiles of concussed athletes are compared with baseline and/or normative data in the absence of baseline scores. However, the cultural equivalence of performance on neuropsychological tests cannot be assumed and has not been sufficiently researched. The purpose of this study was to investigate the neuropsychological test profiles of the ImPACT (Immediate Postconcussion Assessment and Cognitive Testing) on age-matched South African (SA) rugby and US football players. Participants included 11 257 English-speaking, predominantly white male athletes from multiple SA and US schools and sports organizations in 3 age groups: 11 to 13 years (SA, n = 301; US, n = 775); 14 to 16 years (SA, n = 997; US, n = 4081); and 17 to 21 years (SA, n = 319; US, n = 4784). ImPACT neurocognitive composite scores (verbal and visual memory, visual motor speed, reaction time, impulse control) and the ImPACT total symptom score, derived from the initial baseline testing, were used for comparison purposes between the targeted groups. Independent t-test comparisons revealed overall equivalence between the SA and US athletes on the neurocognitive measures, but they also revealed consistently higher symptom scores for SA athletes in association with clinically relevant effect sizes. It was concluded that US neurocognitive normative data on the ImPACT test are appropriate for use on South African athletes whose first language is English, whereas culture-specific sensitivity for symptom reporting on this same population should be taken into consideration for management purposes. It is argued that neurocognitive equivalence is less likely to apply in educationally disadvantaged populations. The use of registered psychologists is deemed necessary to provide contextualized interpretations of computerized test scores, thereby protecting against misdiagnosis that may occur within the concussion management arena via actuarial approaches that fail to take sociocultural complexities into account.